844 A Case of Pulmonary Artery Banding for Future Anatomical Repair in Congenitally Corrected Transposition of the Great Arteries (ccTGA). (12th October 2021) - Banjoko, A; Kumar, A
Abstract: This is a case of a patient prenatally diagnosed with ccTGA. Immediately after birth, postnatal transthoracic echocardiography diagnosed ccTGA with concomitant Ebstein's anomaly of the tricuspid valve, without a ventricular septal defect (VSD). Initially, this dysplastic tricuspid valve had mild tricuspid regurgitation. However, by 12 months follow up, the patient was becoming symptomatic, and their tricuspid regurgitation had become severe. Due to the patients worsening symptoms and regurgitation, clinical intervention was pursued. The patient had Cardiovascular Magnetic Resonance performed to assess for myocardial fibrosis and to measure the size of each ventricle. After imaging and MDT discussion, the patient was deemed suitable for a double switch operation, a form of anatomical repair. However, since this patient did not have pulmonary stenosis (PS), they required a pulmonary artery (PA) band before anatomical repair. This procedure has dual benefits: to retrain the morphological left ventricle (mLV) to cope with systemic pressures, and to induce a septal shift, which can reduce the severity tricuspid regurgitation. At 18 months of age, this patient had their PA band placed. The patient immediately had a reduction in the severity of their tricuspid regurgitation. In the future, this patient will have cardiac catheterisation performed to measure mLV pressures and assess when the patient is ready for anatomical repair. The morphology of this patient is rare, as most patients with ccTGA have an associated VSD. This case describes a potential management pathway for a ccTGA patient without VSD and an Ebstenoid tricuspid valve. It also demonstrates the benefits of PA banding in a ccTGA patient with this morphology. This is a unique contribution, due to the rarity of this specific morphology and the limited evidence and guidance for its successful management.